2014
DOI: 10.1680/geolett.14.00018
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical radial expansion of heat exchanger piles and possible effects on contact pressures at pile–soil interface

Abstract: This letter shows that the increase of heat exchanger pile capacity in response to heating, observed in several small-scale laboratory studies cannot be directly attributed to the increase of contact pressure at the soil/pile interface. The main thermo-hydro-mechanical processes that influence the capacity and behavior of heat exchanger piles include thermal hardening of the soil, thermally induced water flow, excess pore pressure development and volume changes upon thermal consolidation. Due to the lack of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…Evaluation of the radial thermal response will also provide confirmation of the role of pile-soil 5 interface stresses due to radial thermal expansion of energy piles on their ultimate capacity, which has been proposed as a possible mechanism contributing to the side shear resistance of centrifuge-scale energy piles in compacted silt along with changes in effective stress in unsaturated soils associated with thermally induced drying (McCartney and Rosenberg, 2011;Goode and McCartney, 2015). Preliminary numerical and analytical studies using cavity expansion analyses by Olgun et al (2014) and Zhou et al (2016) indicate that no significant changes in pile-soil interface stresses are expected from the radial thermal expansion of the pile. However, these studies have not been validated against field scale studies.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Evaluation of the radial thermal response will also provide confirmation of the role of pile-soil 5 interface stresses due to radial thermal expansion of energy piles on their ultimate capacity, which has been proposed as a possible mechanism contributing to the side shear resistance of centrifuge-scale energy piles in compacted silt along with changes in effective stress in unsaturated soils associated with thermally induced drying (McCartney and Rosenberg, 2011;Goode and McCartney, 2015). Preliminary numerical and analytical studies using cavity expansion analyses by Olgun et al (2014) and Zhou et al (2016) indicate that no significant changes in pile-soil interface stresses are expected from the radial thermal expansion of the pile. However, these studies have not been validated against field scale studies.…”
Section: Introductionmentioning
confidence: 85%
“…Frequent temperature reversals may induce different magnitudes of thermal loads in the pile and at the pile-soil interface compared to monotonic 4 temperature changes. Depending on the soil surrounding the energy pile, thermal cycles could cause fatigue-like processes which could intensify deformations of the pile and the surrounding soil (Suryatriyastuti et al 2013;Olgun et al, 2014;Pasten and Santamarina 2014). Although investigated using numerical simulations for energy piles in idealized soil layers, this cyclic thermal mechanism is not well understood at a field scale.…”
Section: Introductionmentioning
confidence: 99%
“…However, the temperature change of pile foundations during heating and cooling may lead to some irreversible volumetric strain for the surrounding soils [4,5]. It would also cause the changes in the toe resistance and shaft friction along the pile, which would affect the serviceability and stability of pile foundations [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These temperature changes can affect the stress state at the pile-soil interface and the shear strength of the soil that affects the tip resistance (Olgun et al, 2014). Recent studies on the impact of thermal loading at pile-soil interface indicate that the bearing capacity of the pile is not significantly affected (Suguang et al, 2014, Di Donna, 2014, GSHP Association, 2012, Mimouni, 2014, Olgun et al, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…These temperature changes can affect the stress state at the pile-soil interface and the shear strength of the soil that affects the tip resistance (Olgun et al, 2014). Recent studies on the impact of thermal loading at pile-soil interface indicate that the bearing capacity of the pile is not significantly affected (Suguang et al, 2014, Di Donna, 2014, GSHP Association, 2012, Mimouni, 2014, Olgun et al, 2014. Xiao et al (2014) and Di Donna (2014) have analyzed monotonic temperature variations in the range from 6°C to 50°C-60°C and have concluded that higher temperatures increase the strength of the clay-concrete contact and that the sand-concrete interface is not affected by the monotonic temperature changes.…”
Section: Introductionmentioning
confidence: 99%